1999
DOI: 10.1530/eje.0.1400404
|View full text |Cite
|
Sign up to set email alerts
|

Management of differentiated thyroid cancer diagnosed during pregnancy

Abstract: Objective: To assess the outcome of thyroid cancer diagnosed during pregnancy. Design: Retrospective analysis of patients diagnosed between 1949 and 1997 with thyroid cancer presenting during pregnancy. Results: Nine women with a median age of 28 years were identified. A thyroid nodule was discovered by the clinician during routine antenatal examination in four cases, the remainder had noted a lump in the neck. In all patients, the nodule was reported to almost double in size during the pregnancy. One patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…Pregnant women who are diagnosed with thyroid cancer share similar physical findings, pathological tumor features and outcome as those who were not pregnant (73). Treatment in this group of patients is also similar to that in non-pregnant women.…”
Section: Differentiated Thyroid Cancer During Pregnancymentioning
confidence: 74%
“…Pregnant women who are diagnosed with thyroid cancer share similar physical findings, pathological tumor features and outcome as those who were not pregnant (73). Treatment in this group of patients is also similar to that in non-pregnant women.…”
Section: Differentiated Thyroid Cancer During Pregnancymentioning
confidence: 74%
“…One survey found that 4.4% of thyroid cancers in young women were diagnosed during pregnancy [8], and it has been suggested that up to 10% of thyroid cancers that occur in women during their reproductive years are diagnosed during pregnancy or during the first year after delivery [13]. In contrast, our survey of patients over a 13-year period found 1,240 Korean women between 15 and 45 years old who were diagnosed with thyroid cancer, among which 20 cancers were detected during pregnancy, yielding an incidence of 1.6%.…”
Section: Discussionmentioning
confidence: 99%
“…According to the first opinion, since human chorionic gonadotropin released during pregnancy accelerates the growth of thyroid carcinomas [5,6], surgery should be performed during the second trimester rather than postponed until after delivery [7,8]. According to the second opinion, since the prognosis of thyroid cancer detected during pregnancy is similar to the prognosis in nonpregnant woman, surgery should be delayed until after delivery, thus preventing maternal complications and fetal death associated with surgery during pregnancy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery, in the form of thyroidectomy , can safely be performed during the mid-trimester with no increase in adverse maternal or neonatal outcomes [ 110 ]. Alternatively, if a differentiated cancer is noted later in gestation or the patient declines therapy during her pregnancy, surgery can be postponed until after delivery without impacting the long-term prognosis.…”
Section: Thyroid Cancermentioning
confidence: 99%